A scoping study of “Snapshot” teaching framework - Gina Selvira Yanti; Rafika Nurhidayah (Journal on English as a Foreign Language, 2022)
Despite the emergence of Dogme ELT in the 2000s, only small numbers of academic research employing this approach were documented, especially in the context of teaching English Speaking skills in Indonesian higher education. Also, as a response to Indonesian students’ unsatisfied performance in English skills, this study was aimed to introduce and propose an instructional framework using "Snapshot" for college students. As one of the Dogme ELT activities, it hopefully can boost students' motivation, participation, and ability to use the target language orally. Following the scoping study method by Arksey and O’Malley (2005), we gathered data by deriving and concluding theories and practices of research published in 2016 until 2020. As a result, there are thirteen studies on Dogme ELT. From those studies found, we derived and cultivated the implementation of the approach, the perspectives of teachers and students toward the activities, and then presented the proposed framework in teaching English speaking using Snapshot in three stages. Furthermore, the findings indicate that only five out of thirteen studies that empirically utilized and described Dogme ELT in the classroom with mostly favored by both teachers and students. In sum, the proposed framework hopefully can benefit educators in general, ELT teachers, and lecturers in particular.